A Bacteriophage Microgel Effectively Treats the Multidrug-Resistant Acinetobacter baumannii Bacterial Infections in Burn Wounds - Dehari, Deepa; Chaudhuri, Aiswarya; Kumar, Dulla Naveen; Patil, Rohit; Gangwar, Mayank; Rastogi, Sonam; Kumar, Dinesh; Nath, Gopal; Agrawal, Ashish Kumar (Pharmaceuticals (Basel, Switzerland), 2023)
Multidrug-resistant (MDR) Acinetobacter baumannii (A. baumannii) is one of the major pathogens present in burn wound infections. Biofilm formation makes it further challenging to treat with clinically available antibiotics. In the current work, we isolated the A. baumannii-specific bacteriophages (BPABΦ1), loaded into the chitosan microparticles followed by dispersion in gel, and evaluated therapeutic efficacy against MDR A. baumannii clinical strains. Isolated BPABΦ1 were found to belong to the Corticoviridae family, with burst size 102.12 ± 2.65 PFUs per infected host cell. The BPABΦ1 loaded chitosan microparticles were evaluated for quality attributes viz. size, PDI, surface morphology, in vitro release, etc. The developed formulation exhibited excellent antibiofilm eradication potential in vitro and effective wound healing after topical application.